Conversion Surgery in Gastric Cancer Carcinomatosis - Morgagni, Paolo; Solaini, Leonardo; Saragoni, Luca; Monti, Manlio; Valgiusti, Martina; Vittimberga, Giovanni; Frassineti, Giovanni Luca; Framarini, Massimo; Ercolani, Giorgio (Frontiers in Oncology, 2022)
After the REGATTA trial, patients with stage IV gastric cancer could only benefit from chemotherapy (CHT). However, some of these patients may respond extraordinarily to palliative chemotherapy, converting their disease to a radically operable stage. We present a single centre experience in treating peritoneal carcinomatosis from gastric cancer. All patients with stage IV gastric cancer with peritoneal metastases as a single metastatic operated at a single center between 2005-2020 were included. Cases were grouped according to the treatment received. A total of 118 patients were considered, 46 were submitted to palliative gastrectomy (11 were considered M1 because of an unsuspected positive peritoneal cytology), and 20 were submitted to Hyperthermic Intraperitoneal Chemotherapy (HIPEC) because of <6 Peritoneal Cancer Index (PCI). The HIPEC median overall survival (OS) was 46.7 (95% CI 15.8-64.0). Surgery after CHT presented a median OS 14.4 (8.2-26.8) and after upfront surgery 14.7 (10.9-21.1). Patients treated with upfront surgery and considered M1 only because of a positive cytology, had a median OS of 29.2 (25.2-29.2) p=0.050. Considering the HIPEC treated patients, we did not find any difference between the ten patients without any residual carcinomatosis at the resective operation and the ten patients with positive residual cytology or <6 PCI carcinomatosis at surgery and considered R0 at the end of the surgical procedure. Survival rates of patients treated with surgery plus HIPEC were 60.4 months (9.2-60.4) in completely regressed cancer after chemotherapy and 31.2 (15.8-64.0) in those partially regressed (p=0.742). Conversion surgery should also be proposed to a subgroup of peritoneal carcinomatosis gastric cancer patients as it is associated with good survival.